Treatment-Refractory Eosinophilic Esophagitis Successfully Managed with benralizumab: A Case Presentation and literature review - Petrousis Grigorios; Retsas Pavlos; Ignatova Simone; Karapiperis Dimitrios (Sciendo, 2024)
Eosinophilic Esophagitis is a widely-recognized immune-mediated esophagus disease with distinct clinical and histopathological features, exhibiting an increased global incidence. Therapeutic options encompass either dietary measures or pharmacological approaches, including proton pump inhibitors and topical corticosteroids. The use of monoclonal antibodies is currently under comprehensive evaluation, with a plethora of ongoing clinical trials designed to determine their clinical efficacy. The present case report demonstrates an exceptional case of refractory Eosinophilic Esophagitis, unresponsive to conventional treatment, achieving both clinical and histopathological remission subsequent to initiation of benralizumab treatment. Concurrently, our case underscores the necessity for continued research in the field of monoclonal antibodies for their use as a future treatment approach against Eosinophilic Esophagitis.